2019
DOI: 10.3390/ma12203285
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Post Weld Heat Treatment Precipitation on Duplex Stainless Steels Weld Overlay towards Pitting Corrosion

Abstract: Duplex stainless steels (DSSs) are complex materials and they have been widely used in the marine environment and gas industries, primarily offering a better resistance of pitting corrosion and good mechanical properties. In the present work, the effects of heat treatment on duplex stainless steel (DSS) weld overlay samples that were heat treated at three different temperatures, namely 350 °C, 650 °C, and 1050 °C, and followed by air cooling and water quenching were studied. Stress relief temperature at 650 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It has been also found that the application of a post-welding heat treatment on welded duplex stainless steel or on welded X70 steel is beneficial on the mechanical properties because the residual stresses are reduced and the formation of certain undesirable phases is avoided [17,18]. In this context, the objective of this work is to study the microstructural and mechanical evolution during a heat treatment at 200 °C and 600 °C for 2 h of a welded joint of X70 steel with duplex stainless steel assembled by the tungsten gas arc welding process (GTAW).…”
Section: Introductionmentioning
confidence: 99%
“…It has been also found that the application of a post-welding heat treatment on welded duplex stainless steel or on welded X70 steel is beneficial on the mechanical properties because the residual stresses are reduced and the formation of certain undesirable phases is avoided [17,18]. In this context, the objective of this work is to study the microstructural and mechanical evolution during a heat treatment at 200 °C and 600 °C for 2 h of a welded joint of X70 steel with duplex stainless steel assembled by the tungsten gas arc welding process (GTAW).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a weld overlay offers a cost-effective solution as it allows targeted protection in vulnerable areas rather than using expensive alloys throughout the entire structure [13]. Overall, a weld overlay plays a crucial role in enhancing the performance, durability, and cost-effectiveness of essential equipment and infrastructure [14,15]. The weld overlay process is utilized to enhance various surface characteristics of the base metal.…”
Section: Introductionmentioning
confidence: 99%
“…The DSS UNS S32205 (3%Mo, 22%Cr, and 5%Ni) is mainly used in the chemical industry, oil transportation, food, paper and cellulose [9][10][11][12][13] . In these areas, pipes, tanks, and other components require a welding process that does not alter their mechanical and corrosion resistance properties.…”
Section: Introductionmentioning
confidence: 99%